Evaluating biosecurity policy implementation in the seaweed aquaculture industry of Malaysia, using the quantitative knowledge, attitude, and practices (KAP) survey technique. (December 2021) - Kambey, Cicilia S.B.; Campbell, Iona; Cottier-Cook, Elizabeth J.; Nor, Adibi R.M.; Kassim, Azhar; Sade, Ahemad; Lim, Phaik-Eem
Abstract: This study evaluated on-farm implementation and effectiveness of Malaysian seaweed aquaculture policies and regulations that applied the biosecurity concept. The knowledge-attitude-practice (KAP) survey tool was utilised to assess the effectiveness of the biosecurity measures adopted by seaweed stakeholders, including 67 seaweed farmers and ten government extension officers, who were located in the three most productive seaweed producing regions. The KAP results indicated a disconnection between the implementation of biosecurity measures in national policy and uptake by practising farmers. Although farmer's biosecurity knowledge and attitude scores were fair (55.7–64.1%), implementation of practices was poor (36.1–40.6%). The survey data highlighted that a low educational level, combined with the temporary nature of employment in the seaweed sector, contributes to the lower KAP scores. Extension officers are also limited in their ability to support farmers in implementing good biosecurity practices due to their moderate knowledge (57.9%), despite having a good attitude towards biosecurity (76.9%). The implementation of national seaweed policies including biosecurity prevention, and mitigation measures, remains weak due to the limited understanding and ability of the stakeholders to carry out farm risks. By identifying some forthwith gaps, this work highlights where short-term improvements and longer-term goals could be introduced. This study also highlights the importance of translating biosecurity policy into on-the-ground knowledge and stresses the need for economic support to enable a more significant impact in the upstream level of the seaweed aquaculture industry.